Model Konseptual Untuk Penerapan Water Sensitive City Berdasarkan Kesehatan Ekologis Di Kota Sigli - Nurul Maulidia; Halis Agussaini; Fahmi Aulia (Jurnal RAUT, 2023)
Sigli City experiences environmental problems such as floods, the lack of green open space as an infiltration area, to the existence of environmental-based diseases such as diarrhea which always occurs every year. Water Sensitive City (WSC) is a water-friendly city that supports the realization of sustainable development including protecting ecology and water resources. This study was conducted to determine the contribution of the seven WSC index targets in their implementation and identify the dominant factors that affect "Ecological Health" (the fifth WSC index target) to the application of the concept based on existing conditions in Sigli City. The research methods used are analytical hierarchy process (AHP) and Partial Least Square (PLS). Research variables include floods (X1), rainfall (X2), built-up areas (X3), protected areas (X4), water bodies (X5), and environmental-based diseases (X6). Based on the results of the analysis, the contribution values of the 7 most dominant WSC targets are "Water-Friendly Urban Governance" and "Ecological Health" with a value range of 0.2. The value for the Y variable is the score of "Ecological Health" which is 0.985. The results of the PLS test resulted in the factors that most influence "Ecological Health" in the implementation of WSC at the study site, namely floods, water bodies, protected areas and built-up areas (strong relations). Meanwhile, rainfall variables and environmental-based diseases do not greatly affect the contribution of ecological health in application at the study site (weak relationships).